Comparison of efficacy of high dose inhaled corticosteroids with a combination of low dose inhaled corticosteroids and long acting β2 agonists in patients of moderate persistent asthma : a randomised prospective comparative study - Sood, Vivek; Sharma, Parveen; Bansal, Rekha; Kansal, Dinesh (International Journal of Basic & Clinical Pharmacology, 2016)
Background: Asthma has global prevalence varying from 2-25%. Among various subtypes, moderate persistent asthma is a subtype currently managed by a combination therapy of low dose inhaled corticosteroids and LABA (long acting β2 agonists). Search is on for LABA free regime because of safety concerns and increased risk of exacerbations as reported in meta-analysis conducted by FDA in 2008. Methods: Patients (new and old) of either sex and age having moderate persistent asthma as per GINA 2004 guidelines were enrolled and allocated in two groups using block randomization. DPIs (dry powder inhalation) were used in the study. Budecort group subjects were treated with budesonide 400 µg rotacaps twice a day. Foracort group subjects were treated with combination rotacaps of formoterol 6 µg with budesonide 200 µg twice a day. Follow up period in study was nine months with quarterly spirometry assessment. Results: In 63 enrolled cases, there was no significant difference in intergroup spirometry comparison at baseline and at 9 months. The difference at 9 months in spirometry as compared from baseline in each group was also not statistically significant. Numerically, budecort group showed slightly better values. Conclusions: The therapy in each group was comparable in terms of efficacy. This is important due to the fact that therapy in current use for moderate persistent asthma is combination therapy. So use of high dose inhaled steroid therapy used as 400 µg rotacaps with matching revolizer twice a day (800µg daily) may be good alternative to use of combination therapy particularly in patients where LABA cannot be used.